2011
DOI: 10.1029/2010wr009856
|View full text |Cite
|
Sign up to set email alerts
|

Soil water dynamics around a tree on a hillslope with or without rainwater supplied by stemflow

Abstract: [1] A tree can partition rainfall into throughfall and stemflow (SF), causing water to be funneled around the tree base, and can preferentially divert rainwater in soil layers, causing water to be funneled around tree roots. To determine the effects of each on soil water dynamics, we compared soil water dynamics around a tree on a hillslope on the basis of 2 years of field observations before (SF period) and after (non-SF period) intercepting the stemflow of the tree. Additionally, two sprinkling experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 43 publications
8
90
0
2
Order By: Relevance
“…Dye staining experiments have shown that subsurface flow may often take place in living and decayed root channels (e.g. Noguchi et al, 1999;Anderson et al, 2009;Liang et al, 2011). This was confirmed by our study where lateral subsurface flow was promoted by the development of the root network.…”
Section: Interpretation Of Flow Processessupporting
confidence: 89%
See 1 more Smart Citation
“…Dye staining experiments have shown that subsurface flow may often take place in living and decayed root channels (e.g. Noguchi et al, 1999;Anderson et al, 2009;Liang et al, 2011). This was confirmed by our study where lateral subsurface flow was promoted by the development of the root network.…”
Section: Interpretation Of Flow Processessupporting
confidence: 89%
“…In these studies, dye powder was sprinkled on the soil surface around the base of trunks of desert shrubs (MartinezMeza and Whitford, 1996;Li et al, 2009) or dye solution was sprayed toward the downslope side of tree stems of Stewartia plants (Liang et al, 2011). We designed a novel dye tracer experiment for tracking root channelization of stemflow water.…”
Section: Introductionmentioning
confidence: 99%
“…The interception and transpiration of water are responsible for the negative correlations of TBA with soil moisture at depths of 10 and 30 cm in area B under dry conditions (Figure e,j). The impacts of throughfall or stem flow near tree trunks can be a possible explanation under very wet conditions (Liang, Kosugi, & Mizuyama, ) as the spatial distribution of TBA is positively correlated for high levels of soil moisture (Figure j,o). The high density of TBA in the transition zone may be associated with the development of preferential flow patterns, which result from changes in the levels of soil moisture as shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also linked stemflow producing trees to preferential flow through soils (Liang et al 2007(Liang et al , 2009(Liang et al , 2011, illustrating the potential for transport of dissolved nutrients to biogeochemically active watershed areas (e.g., near-stream saturated zones; Vidon et al 2010). …”
Section: Introductionmentioning
confidence: 99%